Uruguay : Ex-Post Evaluation of Exceptional Access Under the 2005 Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2008)
The IMF forged an important partnership with the Uruguayan government aiming to help the country overcome its worst financial and economic crisis. The early termination of the program is seen as a sign of success, primarily for the government and also for the IMF. The delays and the unfinished structural agenda were a disappointment. In future, the government should continue to take advantage of the opportunity offered by the favorable environment to place the economy on a sound footing, and protect it against abrupt market reversals.